Can invasive species replace native species as a resource for birds under climate change? A case study on bird-fruit interactions. (January 2020) - Gallinat, Amanda S.; Primack, Richard B.; Lloyd-Evans, Trevor L.
Highlights: Fruits are important for migratory bird nutrition, and birds disperse seeds. Bird-fruit interactions may be altered by climate change and invasive plants. Invasive plants fruit later than native plants and are more abundant in late-autumn. Birds consume more native fruits throughout the autumn, even when they are rare. Abstract: Wild fruits are an important food source for many north temperate-breeding landbirds during autumn migration and, in turn, birds provide the service of seed dispersal. Despite the importance of these autumn interactions, their potential to shift with climate change and species invasions remains poorly understood. As invasive fleshy-fruited shrubs spread across the Northeast USA and many landbird species pass through stopover sites later with warming temperatures, the potential for changes in bird-fruit interactions depends on the phenology and availability of native and invasive wild fruits, and bird preferences across the autumn season. We observed the fruiting phenology of 25 native and invasive fleshy-fruited wild plant species at Manomet, a migratory stopover site on the coast of Massachusetts, USA, during the autumn migration season (August to November) in 2014 and 2015. We also monitored fruit availability across Manomet in 2015. To determine whether fruit consumption reflected phenology and availability, we identified seeds from 469 fecal samples collected from songbirds captured during the 2014 and 2015 autumn banding seasons. We found that while invasive shrubs fruited later, on average, than native plants, and comprised a large proportion of the total available fruits in late-autumn, birds primarily consumed the fruits of native species throughout the autumn season. Our results demonstrate that native fruits are an important food resource for birds during the autumn migration season and are unlikely to be replaced by abundant fruits of late-season invasive species under climate change.